Dynamic perspectives on globalization and sustainable business in Asia - Ordóñez de Pablos, Patricia, 1975- (Business Science Reference, 2019)
"This book brings together academics, researchers, lecturers, decision makers, policy makers, and practitioners to share new theories, research findings, and case studies, to enhance understanding and collaboration in business, management and technology in Asia now and in the future. The book focuses on Asia, with a special attention to South East Asian countries"--